The Measurements and Interpretations of Gender Equity in European Union - Tamutienė, Ilona (Sociologija. Mintis ir veiksmas, 2004)
This article aims to review and to interpret the gender equity in the political, economical and social areas in the EU. The work is based on Human development perspective and methodology. The article consists of two parts. First part gives an explanation about human development and its measurements methodology such as human development index (HDI), gender-related development index (GDI), gender empowerment measure (GEM). The second part of article argues main thesis: high socioeconomic development automatically does not guarantee equity and equality for both woman and man. According to the data of global Human Development report the greater the gender disparity in basic human development, the lower is a country’s GDI relative to its HDI. Sweden, Latvia, Denmark, Finland have the closest correspondence between HDI and GDI. Ireland, Luxembourg, Austria, Belgium, Greece shows highest gender inequality rates. GEM shows that gender equity gaps in political, economic participation and decisionmaking and power over economic resources exist in all EU states members. HDI, GDI, GEM shows that Lithuania does not reach the average of EU. Article concludes that gender inequality problems exist in each EU country and does not depend directly from economical achievement. The good experience of Scandinavian countries gender policy indicates that for gender equity it is necessary to mainstream gender policy.
Keywords: human development; gender equality; countries of the European Union